2000
DOI: 10.1108/00438020010343408
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the implementation of ISO 9000 quality assurance systems

Abstract: Examines the literature relating to the implementation of quality assurance systems and then uses a questionnaire to a number of organisations and consultants to compare “practice” with “theory”. Analyses the implementation process for quality assurance systems designed to meet the requirements of the ISO 9000 standard to identify the role of the different “actors” to find out which factors facilitate the implementation or make it more difficult. Suggests that the primary motivation for introducing ISO 9000 sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…Employee may misunderstand the benefits of change and avoid it in every possible way, he may fear lack of competence, failure at changing the old way of doing things, or assuming new responsibilities other than his current tasks. Same barrier was pointed out by Lee et al (1999), Fuentes et al (2000), Curry and Kadasah (2002), Hesham and Magd (2007), Al-Najjar and Jawad (2011) and Talib and Rahman (2015). This can be prevented with raising awareness about benefits of implementation and removing misconceptions about quality initiatives, organization should invite employees to participate in the change process rather than oblige them to undergo change, in addition, trainings are important to make employees more secure in their new responsibilities and readier to do things differently.…”
Section: Barriers To Iso 9001:2008 Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…Employee may misunderstand the benefits of change and avoid it in every possible way, he may fear lack of competence, failure at changing the old way of doing things, or assuming new responsibilities other than his current tasks. Same barrier was pointed out by Lee et al (1999), Fuentes et al (2000), Curry and Kadasah (2002), Hesham and Magd (2007), Al-Najjar and Jawad (2011) and Talib and Rahman (2015). This can be prevented with raising awareness about benefits of implementation and removing misconceptions about quality initiatives, organization should invite employees to participate in the change process rather than oblige them to undergo change, in addition, trainings are important to make employees more secure in their new responsibilities and readier to do things differently.…”
Section: Barriers To Iso 9001:2008 Implementationmentioning
confidence: 99%
“…In addition, Respondents believed that lack of internal communication is a barrier to implementation, Fuentes et al (2000), Glover and Siu (2000), Sharif (2005), Burcher et al (2010) and Talib and Rahman (2015) also agreed on poor communication being a significant barrier to managing quality. Main reasons to this barrier are gaps between employees, middle and top management, and lack of coordination between departments.…”
Section: Barriers To Iso 9001:2008 Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that this is double the average percentage worldwide, one could be led to believe that Spanish companies show some problems in ISO 9000 implementation; problems that, although not preventing a large number of initial certifications, do cause many of them to be withdrawn in the long run. A study by Martínez-Fuentes, Balbastre, Escribá, González, and Ardo (2000), in 77 companies and 22 consultants in Spain, revealed a limited implementation of quality management activities that are not directly demanded by ISO 9000. The authors highlight from among these the transfer of degrees of autonomy to employees.…”
Section: After Registration: Now What?mentioning
confidence: 97%
“…Theoretically, efficiency and effectiveness of auditing establishes greater clients' trust on the products/services of the organization and their operations (Fuentes et al, 2000). In a study conducted by Venter and Du Bruyn (2002), the authors showed that audit efficiency and effectiveness requires a strong framework to function as a benchmark standard in order to assess the system and demonstrate its suitable structure, effectiveness and overall functioning.…”
Section: Literature On Efficiency and Effectiveness Of Auditingmentioning
confidence: 99%